Genome-Wide Association Study of Grain Size Traits in Indica Rice Multiparent Advanced Generation Intercross (MAGIC) Population - Ponce, Kimberly; Zhang, Ya; Guo, Longbiao; Leng, Yujia; Ye, Guoyou (Frontiers in Plant Science, 2020)
Rice grain size plays a crucial role in determining grain quality and yield. In this study, two multi-parent advanced generation intercross (MAGIC) populations, DC1 and BIM, were evaluated for grain size across three environments and genotyped with 55K array-based SNP detection and genotype-by-sequencing (GBS), respectively, to identify QTLs and SNPs associated with grain length, grain width, grain length-width ratio, grain thickness and thousand grain weight. A total of 18 QTLs were identified for the five grain size related traits and explained 6.43% to-63.35% of the total phenotypic variance. Twelve of these QTLs co-localized with the cloned genes, GS3, GW5/qSW5, GW7/GL7/SLG7 and GW8/OsSPL16, of which the first two genes showed the strongest effect for grain length and grain width, respectively. Four potential new genes were also identified from the QTLs which exhibited both genetic background independency and environment stability and could be validated in the future studies. Moreover, the significant SNP markers identified are valuable for direct utilization in marker-assisted breeding to improve rice grain size.